The Veterans Affairs Low-Vision Visual Functioning Questionnaire-48 (VA LV VFQ-48): Performance of the Italian version. Issue 5 (September 2020) - Di Maggio, Ilaria; Virgili, Gianni; Giacomelli, Giovanni; Murro, Vittoria; Sato, Giovanni; Amore, Filippo; Villani, Gianfrancesco Maria; Fortini, Stefania; Turco, Simona; Pece, Alfredo; Rizzo, Roberta; Galan, Alessandro; et al.
Purpose: The Veterans Affairs Low-Vision Visual Functioning Questionnaire-48 is among the most validated tools to collect patient-reported outcomes in a low-vision population. We have aimed to conduct a pilot validation of the Italian version of the Veterans Affairs Low-Vision Visual Functioning Questionnaire-48. Methods: The Veterans Affairs Low-Vision Visual Functioning Questionnaire-48 was translated using a standardized procedure and then administered to consecutive low-vision patients attending rehabilitation services in three centers. Patients were interviewed by a trained psychologist regarding the individual items of the tool. Results: We included 131 patients with a mean visual acuity of 0.91 logMAR (standard deviation: 0.42 logMAR), mostly affected by age-related macular degeneration. The Veterans Affairs Low-Vision Visual Functioning Questionnaire-48 showed high internal consistency (Cronbach's alpha: 0.98) and good item-test and item-rest correlation (median: 0.73 and 0.71, respectively). Both the overall score and the subscale (reading, visual motor, mobility and visual information) scores significantly correlated with visual acuity, reading acuity and speed. Reading speed achieved the best absolute correlation with the Veterans Affairs Low-Vision Visual Functioning Questionnaire-48 scores (Spearman r: 0.39–0.49). Conclusion: The Italian version of the Veterans Affairs Low-Vision Visual Functioning Questionnaire-48 is a valid tool to assess patients attending low-vision services. Revising a few items may further improve the tool.